The Pasinetti Paradox in Neoclassical and More General Models: A Correction - Vaughan, R. N. (Review of Economic Studies, 1971)
_S s _ ._ r*k* (k*) S1-Si f(k*) -r*k* I1(k*)9 i.e. the domain of the Pasinetti and Dual solutions in the extended case is dependent on the proportion of workers in each non-capitalist category and the savings propensities of all those categories, as well as on the maximum savings propensity of the capitalist class and the form of the production function. Thus we may note that the maximum extent of the Dual domain occurs when the inequality becomes sl ? oc(k*)sl, the Samuelson-Modigliani condition-when all workers have the same savings propensity (A1 = 1), whilst the minimum extent of the Dual domain occurs when large weight is accorded the worker categories who are minimal savers, when the inequality approaches sl ? scl.